1987
DOI: 10.1002/eji.1830171116
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine proteinase (HuTSP) isolated from a cloned human CD8+ cytolytic T cell line is expressed and secreted by activated CD4+ and CD8+ lymphocytes

Abstract: A novel proteinase, termed human T cell-associated serine proteinase (HuTSP), has been highly purified from a human CD8+ T lymphocyte clone. By using a panel of chromogenic model peptide substrates the enzyme was found to specifically recognize L-arginine and to cleave Tos-Gly-Pro-Arg-nitroanilide with high efficiency at a pH optimum of 10.5-11. Exposure to class-specific proteinase inhibitors revealed that HuTSP is a serine endopeptidase. The enzyme has a mol. mass of approximately 50 kDa (non-reduced) and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In addition to CTLs and NK cells, CD4 ϩ T cells and basophils may express Grs (31,32). Recently, neutrophils also were shown to express Grs (33), although this has been debated by others (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CTLs and NK cells, CD4 ϩ T cells and basophils may express Grs (31,32). Recently, neutrophils also were shown to express Grs (33), although this has been debated by others (34).…”
Section: Discussionmentioning
confidence: 99%
“…The gzmB pathway is normally associated with NK cell and CD8 ϩ T cell responses, but not usually with CD4 ϩ Th cell function (9). Intriguingly, early experiments indicated that granzymes can sometimes be expressed in both murine CD4 ϩ and CD8 ϩ T lymphocytes, albeit at differing levels, depending on the conditions of stimulation and developmental stages of these T cell subsets (10). Recently, gzmB was shown to possess a second function besides its role in target cell killing, being possibly involved in regulating the homeostasis of activated Th2 T cells (11).…”
mentioning
confidence: 99%
“…After 24 h 29.6 IU/ml rpro-uPA or 56% of the melanoma cell-derived prouPA, respectively, were activated by 1 unit/ml HuTSP-1. The amount of HuTSP-1 used for the experiment (1 unit) is secreted by about 3 x lo5 activated UA B34.C7 cells per day [16].…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme, which has also been demonstrated in inflammatory foci in vivo [17], is contained within intracellular storage granules and secreted by vectorially oriented exocytosis upon interaction of T effector cells with appropriate target cells [16]. Under pathophysiological conditions, secreted HuTSP-1 may thus induce the generation of both uPA and plasmin by activating pro-uPA, which has been found in a variety of tissues and cells, including those participating in inflammatory reactions such as macrophages [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation